The good of natural citronella soap and halal certification for Malaysian - Mazita, Mokhtar; Azizan, Azit; Fernando, Yudi; Wan Khairul Anuar, Wan Abd Manan (2022)
This research is considered, as herbal industry in Malaysia. The product is Citronella soap or known as Sabun Serai Wangi. Citronella soap is environmentally friendly product and it can keep the environment from being polluted. Besides the product can also reduces stress with the aroma. It’s social enterprising project. By convincing consumers through halal JAKIM it will definitely have a positive impact on the economy. Easily produced through home made methods. The purpose of this study is to get halal certification. Homemade soap also can help poor or middle income people generate extra income by producing the product with the halal certification.